Welcome the Strangers! Tourism Development, Foreign Direct Investments and Economic Growth in Sub-Saharan Africa - Baidoo, F. (University of Ghana, 2018)
Conventionally, an increase in international tourism receipts coupled with an upsurge in foreign tourist arrivals, into regions with many untapped investment opportunities, is naturally expected to trigger an influx of foreign direct investments (FDI) into such regions. Also, the resulting increase in FDI flows is believed to boost developments across many “green” and viable sectors, including tourism, within the host country upon equitable allocations of such foreign capital. The benefits from these mechanisms potentially include a holistic increase in economic growth in accordance with tourism-led economic growth, and FDI-growth hypotheses. Do these well embraced trends of arguments in literature hold in the case of Sub-Saharan Africa (SSA), in spite of the massive discoveries and booms within the natural mineral resource extraction industries among most SSA countries? Using data from the World Development Indicators (WDI), the study addresses this question by employing System Generalised Methods of Moments (GMM) estimation technique on a dynamic panel data from 42 SSA countries from the year 2000 through 2016. Results show a bilateral causation between FDI and tourism developments, even though, the relationship is negative from FDI to tourism development, and positive from tourism development to FDI. This confirms the tourism-led FDI hypothesis. Further investigations reveal that the impact of general FDI on tourism development is particularly lesser for SSA countries with booming natural mineral extraction sector, and greater for countries with no booming natural mineral extraction sector. This also confirms the presence of the Dutch Disease Syndrome in SSA. Meanwhile, the tourism-led economic growth hypothesis is also evident from this study. Key Words: Dutch Disease, Economic Growth, Foreign Direct Investments, Sub-Saharan Africa, System Generalised Methods of Moments, Tourism Development.
MPhil.
Keywords: Tourism Development; Foreign Direct Investment; Economic Growth; Sub-Saharan Africa